2020
DOI: 10.1093/ckj/sfaa072
|View full text |Cite
|
Sign up to set email alerts
|

Development and external validation of an acute kidney injury risk score for use in the general population

Abstract: Background Improving recognition of patients at increased risk of acute kidney injury (AKI) in the community may facilitate earlier detection and implementation of proactive prevention measures that mitigate the impact of AKI. The aim of this study was to develop and externally validate a practical risk score to predict the risk of AKI in either hospital or community settings using routinely collected data. Methods Routinely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Again, these six selected predictors have been shown to be strongly associated with kidney damage in several studies (Kane-Gill and Goldstein, 2015;Motwani et al, 2018;Zhou et al, 2018;Guan et al, 2019;Wang Q. et al, 2019). In addition, we found that in the initial population of this study, D-AKI patients were older than non-D-AKI patients (median 65 vs. 56 years; p < 0.001), and advanced age has become a major risk factor for AKI due to changes in renal structure and function in older adults, which has been confirmed and incorporated into many AKI risk models (Mehran et al, 2004;Zhou et al, 2018;Bell et al, 2020). In order to find more targeted D-AKI predictors, we balanced demographic data including age; length of hospitalization and duration of suspected drug exposure by propensity score matching.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Again, these six selected predictors have been shown to be strongly associated with kidney damage in several studies (Kane-Gill and Goldstein, 2015;Motwani et al, 2018;Zhou et al, 2018;Guan et al, 2019;Wang Q. et al, 2019). In addition, we found that in the initial population of this study, D-AKI patients were older than non-D-AKI patients (median 65 vs. 56 years; p < 0.001), and advanced age has become a major risk factor for AKI due to changes in renal structure and function in older adults, which has been confirmed and incorporated into many AKI risk models (Mehran et al, 2004;Zhou et al, 2018;Bell et al, 2020). In order to find more targeted D-AKI predictors, we balanced demographic data including age; length of hospitalization and duration of suspected drug exposure by propensity score matching.…”
Section: Discussionsupporting
confidence: 70%
“…Recent studies haves shown that both are mutual risk factors and risk factors for cardiovascular disease (Awdishu and Mehta, 2017). Similarly, eGFR, the main diagnostic indicator of CKD, has been used as an independent predictor by multiple AKI prediction models (Bell et al, 2020;Hu et al, 2020). We also found a significant correlation between alcohol abuse and D-AKI.…”
Section: Discussionsupporting
confidence: 61%
“…Again, these six selected predictors have been shown to be strongly associated with kidney damage in several studies [3,15,21,27,28] . In addition, we found that in the initial population of this study, D-AKI patients were older than non-D-AKI patients (median 65 vs. 56 years; P < 0.001), and advanced age has become a major risk factor for AKI due to changes in renal structure and function in older adults, which has been con rmed and incorporated into many AKI risk models [13,15,26] . In order to nd more targeted D-AKI predictors, we balanced demographic data including age; length of hospitalization and duration of suspected drug exposure by propensity score matching.…”
Section: Discussionmentioning
confidence: 59%
“…The D-AKI risk prediction nomogram was developed by the development group and veri ed in the validation group. Previous research experience has shown that an AUC value greater than 0.7 indicates good predictive performance of the model [21,26] . In our model, the AUC values for the development and validation groups were 0.787 (95%CI: 0.752-0.823) and 0.788 (95%CI: 0.736-0.840), respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation